Production and functional analysis of a phage displayed scFv recombinant antibody targeting EGFR/HER2 dimerization domain - Dabiri, Mina; Tehrani, Mohsen; Rafiei, Alireza; Valadan, Reza (Protein expression and purification, 2025)
Tumor cells exploit epidermal growth factor receptor (EGFR) family to develop resistance against therapeutic antibodies, such as Herceptin. Upon ligand binding, dimerization between EGFR and HER2 is one of the most important causes of treatment failure in breast cancer and other cancers expressing EGFR and HER2. The aim of this study was to develop and evaluate the function of a human recombinant single-chain variable fragment (scFv) antibody against the dimerization domain of EGFR to inhibit its interaction with other members of the epidermal growth factor receptor family, especially HER2. scFv against EGFR was expressed and purified. Cell-ELISA, MTT assay, inhibition of STAT3 phosphorylation, quantitative RT-PCR, and dimerization inhibition were performed on EGFR and HER2 expressing cell lines to characterize functional properties of the produced scFv. The conformational structure of the produced scFv and its binding ability to EGFR was computationally investigated. In vitro binding analysis by cell-ELISA revealed the EGFR binding ability of the purified antibodies and confirmed by immunoblotting. ScFvs preferentially reduced the proliferation and survival of MCF7, MDA-MB-468, and SKOV3 cell lines with no effect on the VERO line. More considerably, MCF7 cells treated with the scFv antibody showed reduced STAT3 phosphorylation, decreased Bcl-2 expression, and increased Bax expression. Finally, the scFvs hindered EGFR and HER2 dimerization. The produced scFv antibody showed to be functional in a simultaneous blockade of EGFR and HER2, suggesting its potential as a promising candidate for targeted therapy against various EGFR overexpressing tumors. •The purified scFv demonstrated selective binding to EGFR-overexpressing cell line and inhibited EGFR/HER2 heterodimerization.•The findings suggest the therapeutic potential of anti-EGFR scFv antibodies in treating various cancers.•Evaluating antibodies targeting the EGFR family, demonstrating anti-proliferative, anti-tumor effects, and selective binding to overexpressing cells.•Engineered scFv induces apoptosis in cancer cells by modulating gene expression of Bcl-2 and Bax, offering promise for treating HER2-related cancers.